2013
DOI: 10.1111/mmi.12278
|View full text |Cite
|
Sign up to set email alerts
|

Random and site‐specific mutagenesis of the Helicobacter pylori ferric uptake regulator provides insight into Fur structure–function relationships

Abstract: Summary The ferric uptake regulator (Fur) of Helicobacter pylori is a global regulator that is important for colonization and survival within the gastric mucosa. H. pylori Fur is unique in its ability to activate and repress gene expression in both the iron-bound (Fe-Fur) and apo forms (apo-Fur). In the current study we combined random and site-specific mutagenesis to identify amino acid residues important for both Fe-Fur and apo-Fur function. We identified 25 mutations that affected Fe-Fur repression and 23 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(104 reference statements)
2
9
0
Order By: Relevance
“…The Fur R88H and P45T mutations are each located close to Fur amino acid residues important for iron coordination of Fur (E90 and H42, respectively) (55), and therefore, we speculate that these mutations might affect the ability of Fur to regulate its target genes. Consistent with this hypothesis, several mutations close to Fur R88 (e.g., R87Q, Y89C, and E90Q) are known to impair Fur regulatory activity (56). Although substitution mutations at the Fur R88 position are not found commonly in H. pylori isolates from humans, an R88H mutation identical to the mutation observed in the present study has been detected in at least three H. pylori isolates from humans (57).…”
Section: Figsupporting
confidence: 73%
“…The Fur R88H and P45T mutations are each located close to Fur amino acid residues important for iron coordination of Fur (E90 and H42, respectively) (55), and therefore, we speculate that these mutations might affect the ability of Fur to regulate its target genes. Consistent with this hypothesis, several mutations close to Fur R88 (e.g., R87Q, Y89C, and E90Q) are known to impair Fur regulatory activity (56). Although substitution mutations at the Fur R88 position are not found commonly in H. pylori isolates from humans, an R88H mutation identical to the mutation observed in the present study has been detected in at least three H. pylori isolates from humans (57).…”
Section: Figsupporting
confidence: 73%
“…Gilbreath et al. characterized Fur by targeted and random mutagenesis and found novel structural features which enable the protein to exert its function in its iron‐bound and unloaded conformation. In addition to playing with host iron supplies, H. pylori is auxotrophic for cholesterol which it takes up from human cells, making use again of host supplies for its own good.…”
Section: Host and Bacteria Interplay: Evolution Of Virulence Factorsmentioning
confidence: 99%
“…The Fur regulator appears to play an important role in environmental adaptation of H. pylori in vivo, including the bacterial response to local iron availability, and backing up the interplay of virulence factors such as VacA and the cagPAI with iron. Gilbreath et al [35] characterized Fur by targeted and random mutagenesis and found novel structural features which enable the protein to exert its function in its ironbound and unloaded conformation. In addition to playing with host iron supplies, H. pylori is auxotrophic for cholesterol which it takes up from human cells, making use again of host supplies for its own good.…”
Section: Host and Bacteria Interplay: Evolution Of Virulence Factorsmentioning
confidence: 99%
“…Combined with the crystal structure of CjFurZn, these observations suggest that the S3 site plays two important functions in CjFur biology, in contributing to S2 metalation and in correctly aligning the DNA binding domain of CjFur for the control of apo-regulated genes. Previous studies documented a similar interplay in Bacillus subtilis and Helicobacter pylori Fur showing that mutation of the S3 site impacts the incorporation of metals in both metal binding sites 39 , 40 . However, we note that BsFur mutants in S2/S3 were unaffected in DNA binding under saturating manganese conditions while CjFur ΔS2 and CjFur ΔS3 mutants showed defects even under 500 molar excess of manganese.…”
Section: Discussionmentioning
confidence: 64%